Teologi Kerja Paulus (2 Tesalonika 3:10-11): Peran Gereja Mengatasi Pengangguran Generasi Z - APRILIO TITUS GUMELAR; SUGIONO SUGIONO (Institut Agama Kristen Negeri Kupang, 2026)
Unemployment among Generation Z presents a serious challenge amidst the digital economic shift affecting social and spiritual aspects. This study aims to address: how Paul’s theology of work in 2 Thessalonians 3:10–12 is understood and what its implications are for the role of the church. The method employed is a qualitative approach through biblical exegesis and hermeneutics, supported by a literature review. The research findings indicate that work is a responsibility of faith that rejects passivity and dependency, and forms part of the Christian witness of life. Based on these findings, the church is understood as an agent of transformation that plays a role in shaping the work ethic, self-reliance, and responsibility of the younger generation. Consequently, the church needs to develop an integrative programme combining spirituality and economic empowerment as a concrete response to Generation Z unemployment.